Gene expression-based prediction of pazopanib efficacy in sarcoma - Heilig, Christoph E.; Laßmann, Andreas; Mughal, Sadaf S.; Mock, Andreas; Pirmann, Sebastian; Teleanu, Maria-Veronica; Renner, Marcus; Andresen, Carolin; Köhler, Bruno Christian; Aybey, Bogac; Bauer, Sebastian; Siveke, Jens T.; et al. (European journal of cancer, 2022)
The multi-receptor tyrosine kinase inhibitor pazopanib is approved for the treatment of advanced soft-tissue sarcoma and has also shown activity in other sarcoma subtypes. However, its clinical efficacy is highly variable, and no reliable predictors exist to select patients who are likely to benefit from this drug.